Lithium iron phosphate positive electrode material for lithium ion battery and preparation method of lithium iron phosphate positive electrode material
By doping sodium manganese into the lithium iron phosphate positive electrode material and forming a composite cladding layer of MXene/reduced graphene oxide, the problems of poor conductivity and low lithium ion diffusion rate are solved, and the electrochemical performance and cyclic stability of the material are significantly improved.
Patent Information
- Application Number
- CN202510424780.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-06-24
AI Technical Summary
The existing lithium iron phosphate positive electrode materials have problems such as poor conductivity, low diffusion rate of lithium ions, and difficulty in taking into account both conductivity and structural stability.
By mixing sodium carbonate, manganese carbonate, lithium carbonate and iron phosphate, sodium manganese co-doped lithium iron phosphate powder is obtained, and a composite cladding layer of MXene/reduced graphene oxide and carbon is formed on its surface, and the conductivity and cyclic stability of the material are improved by microwave treatment.
The lithium ion diffusion coefficient and conductivity of the positive electrode material of lithium-ion battery is improved, the rate performance and cycle stability of the material are enhanced, and the cycle life of the battery is extended.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron phosphate positive electrode material for lithium ion batteries and a preparation method thereof. Background Art
[0002] As a secondary chemical energy storage system, lithium-ion batteries are widely used in electric vehicles, aerospace, military weapons and other fields due to their good stability, high conversion efficiency, high specific capacity, low cost, and green environmental protection. The transition from traditional fossil energy to new energy is imminent, especially in the automotive field. Pure electric vehicles are the general trend of future automotive development. At present, the batteries that power electric vehicles are mainly lead-acid batteries, nickel-metal hydride batteries and lithium-ion batteries. Lead-acid batteries are limited in their use in medium and large electric vehicles due to their serious self-discharge, low specific capacity, and environmental pollution; nickel-metal hydride batteries have high self-discharge efficiency and high cost, which limit their large-scale commercial application; and lithium-ion batteries happen to make up for the above shortcomings and have very good application prospects in the field of electric vehicles.
[0003] The performance and cost of lithium-ion batteries are mainly determined by the positive electrode materials, so people continue to deepen their research on positive electrode materials. Among the many positive electrode materials, lithium iron phosphate (LiFePO4) is widely recognized for its advantages such as low cost, long cycle life and high safety. The theoretical energy density of lithium iron phosphate materials is high, and its own stable olivine structure also gives it good thermal stability, cycle stability and safety. However, the low lithium ion diffusion coefficient and low electronic conductivity inhibit the electrochemical performance of LiFePO4. The current improvement measures mainly include: ① Particle nano-size: Control the growth of LiFePO4 to obtain nanoparticles, shorten Li + 1. Migration path within the lattice to increase its diffusion rate; 2. Conductive agent coating: Coating carbon materials, metal elements, oxides and other conductive agents on the surface of LiFePO4 to accelerate electron transfer. Carbon materials are the most commonly used due to their high conductivity, good electrochemical stability, low density, high mechanical strength and low cost; 3. Element doping: Doping LiFePO4 with elements such as Nb, Mg, V, Ti, etc. to increase its lithium ion diffusion coefficient and intrinsic electronic conductivity by reducing the order of the lattice. However, the existing single modification method can only improve the conductivity and cycle performance of lithium iron phosphate materials to a certain extent. Therefore, the existing lithium iron phosphate positive electrode materials have defects such as poor conductivity, low lithium ion diffusion rate, and difficulty in balancing conductivity and structural stability, which makes the use of this technology very limited. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium iron phosphate positive electrode material for lithium ion batteries and a preparation method thereof, to solve the following technical problems: Existing lithium iron phosphate cathode materials have problems such as poor electrical conductivity, low lithium ion diffusion rate, and difficulty in balancing electrical conductivity and structural stability.
[0005] The object of the present invention can be achieved by the following technical solutions: A preparation method of a lithium iron phosphate cathode material for a lithium ion battery, at least including the following preparation steps: Mix sodium carbonate, manganese carbonate, lithium carbonate and iron phosphate, ball mill and then calcine to obtain sodium and manganese co-doped lithium iron phosphate powder; Disperse MXene in deionized water, add graphene oxide, ascorbic acid and glucose, and obtain modified powder after drying; Add the modified powder and surfactant to ethylene glycol, mix evenly to obtain a modified slurry; Add the modified slurry to the sodium and manganese co-doped lithium iron phosphate powder, and perform microwave treatment to obtain a lithium iron phosphate cathode material for a lithium ion battery.
[0006] As a further scheme of the present invention: the molar ratio of the sodium carbonate, the manganese carbonate, the lithium carbonate and the iron phosphate is 1-3:2-5:105-110:100.
[0007] As a further scheme of the present invention: the mass ratio of the MXene, the graphene oxide, the glucose and the ascorbic acid is 1-5:1-5:5-10:1-3.
[0008] As a further scheme of the present invention: the mass ratio of the modified powder, the surfactant and the ethylene glycol is 8-23:0.1-0.3:4-10.
[0009] As a further scheme of the present invention: the mass ratio of the MXene, the graphene oxide, the glucose and the sodium and manganese co-doped lithium iron phosphate powder is 1-5:1-5:5-10:100.
[0010] As a further scheme of the present invention: the MXene is selected from one or a mixture of several of Ti3C2, Zr3C2, Ti4C3 or V4C3, and the surfactant is selected from at least one of cetyltrimethylammonium bromide, polysorbate and alkylphenol polyoxyethylene ether.
[0011] As a further scheme of the present invention: the calcination temperature is 700-850 °C and the time is 10-12 h.
[0012] As a further scheme of the present invention: the microwave treatment temperature is 600-700 °C and the heat preservation time is 20-40 min.
[0013] A lithium iron phosphate cathode material for a lithium-ion battery, which is prepared by the preparation method of the lithium iron phosphate cathode material for a lithium-ion battery described in any one of the above.
[0014] As a further solution of the present invention: the lithium iron phosphate cathode material for a lithium-ion battery at least includes a sodium-manganese co-doped lithium iron phosphate matrix, and a composite coating layer of MXene / reduced graphene oxide and carbon coated on the surface of the lithium iron phosphate matrix.
[0015] The beneficial effects of the present invention: In the present invention, a sodium-manganese co-doped lithium iron phosphate matrix is obtained by co-calcining precursors. Sodium ions and manganese ions enter the lithium iron phosphate lattice, causing it to expand and the lattice volume to increase, expanding the lithium ion migration channels and providing more space for lithium ion insertion / extraction. Further, a coating layer in which Mxene nanosheets and reduced graphene oxide sheets intertwined with carbon layers filling the gaps is formed on the surface of the sodium-manganese co-doped lithium iron phosphate matrix. The carbon layer provides a particle diffusion channel, enhances the conductivity of particles and surface electrons, reduces battery polarization, forms a good high-efficiency transmission network between Mxene and graphene, and improves the ion and electron transmission efficiency, thereby enabling the cathode material to obtain excellent rate performance and good cycle stability. The lithium iron phosphate cathode material for a lithium-ion battery obtained in the present invention effectively improves the capacity performance, rate performance, and cycle life of the lithium-ion battery through dual modification of element doping and conductive agent coating of lithium iron phosphate.
[0016] In the present invention, a sodium-manganese co-doped lithium iron phosphate matrix is obtained through a wet ball milling and precursor co-calcination process. On the one hand, the radii of the doped Mn atoms and Na atoms are both larger than the corresponding replaced atoms, and their entry into the lattice easily causes it to expand. The increase in the lattice volume of the cathode material can provide more space for the deintercalation and intercalation of lithium ions, which is beneficial to the migration of lithium ions in the lattice, can improve the lithium ion diffusion coefficient and conductivity of the material, and thus improve its electrochemical performance. On the other hand, sodium-manganese co-doping causes lattice distortion of lithium iron phosphate, generating more ion vacancies, increasing the carrier concentration and ionic conductivity, weakening battery polarization, improving the capacity retention rate, and enabling the material to exhibit excellent high-rate performance and cycle stability in electrochemical performance.
[0017] In the present invention, MXene, graphene oxide, glucose, ascorbic acid, and a surfactant are added during the formation stage of the coating layer. Under the action of the surfactant, the sodium-manganese co-doped lithium iron phosphate matrix forms an efficient coating structure with MXene and reduced graphene oxide after low-temperature microwave treatment. Moreover, glucose undergoes pyrolytic carbonization under high-temperature microwave treatment to generate an amorphous carbon layer, which coats the surface of the lithium iron phosphate particles and synergistically constructs a "point-plane" conductive network with MXene / reduced graphene oxide. In the present invention, ascorbic acid partially reduces the oxygen-containing functional groups on the surface of graphene oxide to restore the conjugated structure of graphene, forming reduced graphene oxide, retaining the two-dimensional sheet structure, and simultaneously enhancing its electrical conductivity. Subsequent microwave heat treatment further promotes the deep reduction of graphene oxide and repairs the lattice defects of reduced graphene oxide. At the same time, the rapid heating characteristic of microwave avoids the decomposition of MXene caused by long-term high-temperature exposure, and the reducing gas generated by the decomposition of glucose at high temperature can assist ascorbic acid to further reduce GO and protect MXene from oxidation. Through the synergistic effect of ascorbic acid and glucose, the present invention forms a coating layer in which reduced graphene oxide sheets and MXene nanosheets are intertwined on the surface of the sodium-manganese co-doped lithium iron phosphate substrate. Moreover, glucose is carbonized and embedded in the sheet gaps of the MXene and reduced graphene oxide composite material during the microwave treatment stage. The obtained cathode material has good stability, has many advantages such as a short ion transport distance and two-dimensional MXene modification, and can further improve lithium ion diffusion and electronic conductivity on the basis of sodium and manganese doping modification, thereby improving the rate performance and cycle stability of the material. Detailed implementation manners
[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Apparently, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0019] Embodiment 1 The preparation method of MXene includes at least the following steps: After adding 50 mL of deionized water to 150 mL of concentrated hydrochloric acid, 10 g of LiF is added and stirred until completely dissolved. Then, 10 g of Ti3C2 is added to the mixed solution, and the mixture is stirred thoroughly in an oil bath at 40 °C for 72 h. After stirring is completed, the product is washed thoroughly with deionized water until the pH is 7, and the product is freeze-dried for 24 h to obtain MXene powder.
[0020] Embodiment 2 The preparation method of graphene oxide includes at least the following steps: Weigh 10 g of graphite and put it into a mixture containing 120 mL of concentrated sulfuric acid, 25 g of K2S2O8 and 25 g of P2O5, and heat it to 80 °C, stir it in an oil bath for 5 h. After the reaction is completed, wash it thoroughly with deionized water, filter it, and freeze-dry the product for 24 h to obtain graphene oxide.
[0021] Example 3 The preparation method of the lithium iron phosphate cathode material for lithium-ion batteries includes the following steps: Put 1 g of sodium carbonate (Na2CO3), 1.6 g of manganese carbonate (MnCO3), 36.5 g of lithium carbonate (Li2CO3) and 87 g of iron phosphate (FePO4·2H2O) into a ball mill jar, use ethanol as the medium, the ball-to-material ratio is 10:1, the rotation speed is 300 rpm, wet ball mill for 6 hours, after vacuum drying at 80 °C for 12 h, add it to a tube furnace, heat it to 700 °C at a rate of 5 °C / min, calcine it in an argon atmosphere for 10 hours, cool it naturally and then grind and sieve it to obtain sodium and manganese co-doped lithium iron phosphate powder; Disperse 2 g of MXene in 100 mL of deionized water, ultrasonically treat it for 30 min, add 3 g of graphene powder, 1.5 g of ascorbic acid and 5 g of glucose, stir it at 60 °C for 4 h, centrifuge to collect the precipitate, and vacuum dry it at 80 °C to obtain the modified powder; Add the above-mentioned modified powder and 0.1 g of surfactant cetyltrimethylammonium bromide to 10 mL of ethylene glycol, mix them evenly to obtain the modified slurry; Add the above-mentioned modified slurry to the above-mentioned 100 g of sodium and manganese co-doped lithium iron phosphate powder, ball mill for 2 h, then put it into a microwave reactor, under argon protection, heat it to 650 °C at a rate of 20 °C / min, keep it warm for 30 min, cool it and then grind it to obtain the lithium iron phosphate cathode material for lithium-ion batteries.
[0022] Example 4 The preparation method of the lithium iron phosphate cathode material for lithium-ion batteries includes the following steps: Put 1 g of sodium carbonate (Na2CO3), 2.2 g of manganese carbonate (MnCO3), 36.5 g of lithium carbonate (Li2CO3) and 87 g of iron phosphate (FePO4·2H2O) into a ball mill jar, use ethanol as the medium, the ball-to-material ratio is 10:1, the rotation speed is 300 rpm, wet ball mill for 6 hours, after vacuum drying at 80 °C for 12 h, add it to a tube furnace, heat it to 700 °C at a rate of 5 °C / min, calcine it in an argon atmosphere for 10 hours, cool it naturally and then grind and sieve it to obtain sodium and manganese co-doped lithium iron phosphate powder; Disperse 2 g of MXene in 100 mL of deionized water, ultrasonically treat it for 30 min, add 3 g of graphene powder, 1.5 g of ascorbic acid and 5 g of glucose, stir it at 60 °C for 4 h, centrifuge to collect the precipitate, and vacuum dry it at 80 °C to obtain the modified powder; Add the above-mentioned modified powder and 0.1 g of surfactant cetyltrimethylammonium bromide to 10 mL of ethylene glycol, mix evenly to obtain a modified slurry; Add the above-mentioned modified slurry to the above 100 g of sodium and manganese co-doped lithium iron phosphate powder, ball mill for 2 h, then place it in a microwave reactor, under argon protection, heat it to 650 °C at a rate of 20 °C / min, keep it warm for 30 min, cool it and then grind it to obtain the lithium iron phosphate cathode material for lithium-ion batteries.
[0023] Example 5 The preparation method of the lithium iron phosphate cathode material for lithium-ion batteries includes the following steps: Put 1 g of sodium carbonate (Na2CO3), 1.6 g of manganese carbonate (MnCO3), 36.5 g of lithium carbonate (Li2CO3) and 87 g of iron phosphate (FePO4·2H2O) into a ball mill tank, use ethanol as the medium, the ball-to-material ratio is 10:1, the rotation speed is 300 rpm, wet ball mill for 6 hours, after vacuum drying at 80 °C for 12 h, add it to a tube furnace, heat it to 700 °C at a rate of 5 °C / min, calcine in an argon atmosphere for 10 hours, naturally cool it and then grind and screen it to obtain sodium and manganese co-doped lithium iron phosphate powder; Disperse 3 g of MXene in 100 mL of deionized water, ultrasonically treat it for 30 min, add 2 g of graphene powder, 1 g of ascorbic acid and 5 g of glucose, stir at 60 °C for 4 h, centrifuge to collect the precipitate, and obtain the modified powder after vacuum drying at 80 °C; Add the above-mentioned modified powder and 0.1 g of surfactant cetyltrimethylammonium bromide to 10 mL of ethylene glycol, mix evenly to obtain a modified slurry; Add the above-mentioned modified slurry to the above 100 g of sodium and manganese co-doped lithium iron phosphate powder, ball mill for 2 h, then place it in a microwave reactor, under argon protection, heat it to 650 °C at a rate of 20 °C / min, keep it warm for 30 min, cool it and then grind it to obtain the lithium iron phosphate cathode material for lithium-ion batteries.
[0024] Example 6 The preparation method of the lithium iron phosphate cathode material for lithium-ion batteries includes the following steps: Put 1 g of sodium carbonate (Na2CO3), 1.6 g of manganese carbonate (MnCO3), 36.5 g of lithium carbonate (Li2CO3) and 87 g of iron phosphate (FePO4·2H2O) into a ball mill tank, use ethanol as the medium, the ball-to-material ratio is 10:1, the rotation speed is 300 rpm, wet ball mill for 6 hours, after vacuum drying at 80 °C for 12 h, add it to a tube furnace, heat it to 700 °C at a rate of 5 °C / min, calcine in an argon atmosphere for 10 hours, naturally cool it and then grind and screen it to obtain sodium and manganese co-doped lithium iron phosphate powder; Disperse 2 g of MXene in 100 mL of deionized water, ultrasonically treat for 30 min, add 3 g of graphene powder, 1.5 g of ascorbic acid and 8 g of glucose, stir at 60 °C for 4 h, centrifuge to collect the precipitate, and obtain the modified powder after drying in vacuo at 80 °C; Add the above-mentioned modified powder and 0.1 g of the surfactant cetyltrimethylammonium bromide to 10 mL of ethylene glycol, mix evenly to obtain the modified slurry; Add the above-mentioned modified slurry to the above-mentioned 100 g of sodium and manganese co-doped lithium iron phosphate powder, ball mill for 2 h, then place it in a microwave reactor, under argon protection, heat up to 650 °C at a rate of 20 °C / min, hold for 30 min, cool and then grind to obtain the lithium iron phosphate cathode material for lithium-ion batteries.
[0025] Comparative Example 1 The preparation method of the lithium iron phosphate cathode material for lithium-ion batteries includes the following steps: Place 36.5 g of lithium carbonate (Li2CO3) and 87 g of iron phosphate (FePO4·2H2O) in a ball mill tank, use ethanol as the medium, the ball-to-material ratio is 10:1, the rotation speed is 300 rpm, wet ball mill for 6 hours, after drying in vacuo at 80 °C for 12 h, add it to a tube furnace, heat up to 700 °C at a rate of 5 °C / min, calcine in an argon atmosphere for 10 hours, naturally cool and then grind and screen to obtain lithium iron phosphate powder; Disperse 2 g of MXene in 100 mL of deionized water, ultrasonically treat for 30 min, add 3 g of graphene powder, 0.8 g of ascorbic acid and 5 g of glucose, stir at 60 °C for 4 h, centrifuge to collect the precipitate, and obtain the modified powder after drying in vacuo at 80 °C; Add the above-mentioned modified powder and 0.1 g of the surfactant cetyltrimethylammonium bromide to 10 mL of ethylene glycol, mix evenly to obtain the modified slurry; Add the above-mentioned modified slurry to the above-mentioned 100 g of lithium iron phosphate powder, ball mill for 2 h, then place it in a microwave reactor, under argon protection, heat up to 650 °C at a rate of 20 °C / min, hold for 30 min, cool and then grind to obtain the lithium iron phosphate cathode material for lithium-ion batteries.
[0026] Comparative Example 2 The preparation method of the lithium iron phosphate cathode material for lithium-ion batteries includes the following steps: 1 g of sodium carbonate (Na2CO3), 1.6 g of manganese carbonate (MnCO3), 36.5 g of lithium carbonate (Li2CO3) and 87 g of iron phosphate (FePO4·2H2O) were placed in a ball milling jar. Using ethanol as the medium, with a ball-to-material ratio of 10:1 and a rotation speed of 300 rpm, wet ball milling was carried out for 6 hours. After vacuum drying at 80 °C for 12 h, it was added to a tube furnace and heated to 700 °C at a rate of 5 °C / min, and calcined in an argon atmosphere for 10 hours. After natural cooling, it was ground and sieved to obtain sodium and manganese co-doped lithium iron phosphate powder, which was used as the lithium iron phosphate cathode material for lithium-ion batteries.
[0027] Comparative Example 3 The preparation method of the lithium iron phosphate cathode material for lithium-ion batteries includes the following steps: 1 g of sodium carbonate (Na2CO3), 1.6 g of manganese carbonate (MnCO3), 36.5 g of lithium carbonate (Li2CO3) and 87 g of iron phosphate (FePO4·2H2O) were placed in a ball milling jar. Using ethanol as the medium, with a ball-to-material ratio of 10:1 and a rotation speed of 300 rpm, wet ball milling was carried out for 6 hours. After vacuum drying at 80 °C for 12 h, it was added to a tube furnace and heated to 700 °C at a rate of 5 °C / min, and calcined in an argon atmosphere for 10 hours. After natural cooling, it was ground and sieved to obtain sodium and manganese co-doped lithium iron phosphate powder; 2 g of MXene was dispersed in 100 mL of deionized water, ultrasonicated for 30 min, 3 g of graphene powder and 5 g of glucose were added, and stirred at 60 °C for 4 h. The precipitate was collected by centrifugation and vacuum dried at 80 °C to obtain the modified powder; The above modified powder and 0.1 g of the surfactant cetyltrimethylammonium bromide were added to 10 mL of ethylene glycol and mixed evenly to obtain the modified slurry; The above modified slurry was added to the above 100 g of sodium and manganese co-doped lithium iron phosphate powder. After ball milling for 2 h, it was placed in a microwave reactor and heated to 650 °C at a rate of 20 °C / min under argon protection, held for 30 min, and ground after cooling to obtain the lithium iron phosphate cathode material for lithium-ion batteries.
[0028] Comparative Example 4 The preparation method of the lithium iron phosphate cathode material for lithium-ion batteries includes the following steps: 1 g of sodium carbonate (Na2CO3), 1.6 g of manganese carbonate (MnCO3), 36.5 g of lithium carbonate (Li2CO3) and 87 g of iron phosphate (FePO4·2H2O) were placed in a ball milling jar. Using ethanol as the medium, with a ball-to-material ratio of 10:1 and a rotation speed of 300 rpm, wet ball milling was carried out for 6 hours. After vacuum drying at 80 °C for 12 h, it was added to a tube furnace and heated to 700 °C at a rate of 5 °C / min, and calcined in an argon atmosphere for 10 hours. After natural cooling, it was ground and sieved to obtain sodium and manganese co-doped lithium iron phosphate powder; Disperse 2 g of MXene in 100 mL of deionized water, ultrasonically treat for 30 min, add 3 g of graphene powder and 1.5 g of ascorbic acid, stir at 60 °C for 4 h, centrifuge to collect the precipitate, and obtain the modified powder after drying in vacuum at 80 °C; Add the above-mentioned modified powder and 0.1 g of surfactant cetyltrimethylammonium bromide to 10 mL of ethylene glycol, mix evenly to obtain the modified slurry; Add the above-mentioned modified slurry to 100 g of sodium-manganese co-doped lithium iron phosphate powder, ball mill for 2 h, place it in a microwave reactor, under argon protection, heat up to 650 °C at a rate of 20 °C / min, hold for 30 min, cool and then grind to obtain the lithium iron phosphate cathode material for lithium-ion batteries.
[0029] Prepare the battery: a. Preparation of the negative electrode sheet: Dissolve the negative electrode active material, conductive carbon black, binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose in deionized water in a mass ratio of 92:2:5:1, mix evenly to make the negative electrode slurry, then evenly coat the negative electrode slurry on the negative electrode current collector copper foil, then dry at 85 °C and perform cold pressing, and then perform edge cutting, slicing, striping, and welding of the tab to prepare the negative electrode sheet.
[0030] b. Preparation of the positive electrode sheet: Dissolve the lithium iron phosphate cathode material for lithium-ion batteries, conductive carbon black, and binder polyvinylidene fluoride obtained in Examples 3-6 and Comparative Examples 1-2 in N-methylpyrrolidone in a mass ratio of 96:2:2, mix evenly to make the positive electrode slurry, then evenly coat the positive electrode slurry on the positive electrode current collector aluminum foil, then dry at 85 °C and perform cold pressing, edge cutting, slicing, striping, and welding of the tab to prepare the positive electrode sheet.
[0031] c. Battery assembly: Wind the positive electrode sheet, negative electrode sheet, and separator (a polypropylene microporous membrane with a thickness of 12 μm) through a winding process to make an electrode core, then encapsulate it with an aluminum-plastic film and inject the electrolyte. The electrolyte uses 1 M LiPF6 as the lithium salt, and the organic solvent uses EC / EMC = 3:7 (volume ratio). After that, complete the preparation of the lithium-ion battery through processes such as formation, capacity measurement, and shaping.
[0032] Electrochemical performance detection: Use the LAND battery test system to perform electrochemical performance tests on the batteries prepared from the modified graphite electrode materials obtained by the preparation methods of Examples 3-6 and Comparative Examples 1-4. The voltage test range is 0.01 - 3.0 V, the test temperature is 25 °C, and the test results are shown in the following table: As can be seen from the data in the above table, the battery prepared from the lithium iron phosphate cathode material obtained by the preparation methods provided in Examples 3-6 of the present invention has a high initial reversible capacity and initial Coulomb efficiency, and has excellent capacity performance, rate performance and cycle performance. In Comparative Example 1, sodium and manganese elements were not doped, and in Comparative Example 2, coating modification was not carried out. The measured capacity performance, rate performance and cycle performance of the battery prepared from the lithium iron phosphate cathode material were all reduced, indicating that the dual modification of element doping and conductive agent coating of lithium iron phosphate is more effective than single modification in improving the capacity, rate performance and cycle life of the cathode material. In the coating modification stage, ascorbic acid was not added in Comparative Example 3, and glucose was not added in Comparative Example 4. The measured capacity performance, rate performance and cycle performance of the battery prepared from the lithium iron phosphate cathode material all decreased, indicating that glucose and ascorbic acid have a synergistic effect, which can improve the coating effect of carbon layer, MXene and reduced graphene oxide, and can effectively improve the capacity performance, rate performance and cycle performance of lithium ion batteries.
[0033] The above has described in detail one embodiment of the present invention, but the content described is only the preferred embodiment of the present invention and cannot be considered as limiting the scope of implementation of the present invention. All equivalent changes and improvements made according to the scope of the present invention application should still fall within the scope covered by the patent of the present invention.
Claims
1. A method for preparing a lithium iron phosphate positive electrode material for a lithium ion battery, characterized in that: The method comprises at least the following preparation steps: Sodium carbonate, manganese carbonate, lithium carbonate and iron phosphate are mixed, ball-milled and then calcined to obtain sodium-manganese co-doped lithium iron phosphate powder; MXene was dispersed in deionized water, graphene oxide, ascorbic acid and glucose were added, and modified powder was obtained after drying; Adding the modified powder and surfactant into ethylene glycol, mixing evenly, to obtain a modified slurry; The modified slurry is added to the sodium-manganese co-doped lithium iron phosphate powder, and subjected to microwave treatment to obtain a lithium iron phosphate positive electrode material for a lithium ion battery.
2. The method for preparing a lithium iron phosphate positive electrode material for a lithium ion battery according to claim 1, characterized in that: The molar ratio of the sodium carbonate, the manganese carbonate, the lithium carbonate and the iron phosphate is 1-3:2-5:105-110:
100.
3. The method for preparing a lithium iron phosphate positive electrode material for a lithium ion battery according to claim 1, characterized in that: The mass ratio of the MXene, the graphene oxide, the glucose and the ascorbic acid is 1-5:1-5:5-10:1-3.
4. The method for preparing a lithium iron phosphate positive electrode material for a lithium ion battery according to claim 1, characterized in that: The mass ratio of the modified powder, the surfactant and the ethylene glycol is 8-23:0.1-0.3:4-10.
5. The method for preparing a lithium iron phosphate positive electrode material for a lithium ion battery according to claim 3, characterized in that: The mass ratio of the MXene, the graphene oxide, the glucose and the sodium manganese co-doped lithium iron phosphate powder is 1-5:1-5:5-10:
100.
6. 根据权利要求1所述的一种锂离子电池用磷酸铁锂正极材料的制备方法,其特征在于, The MXene is selected from one or a mixture of Ti3C2, Zr3C2, Ti4C3 or V4C3, and the surfactant is selected from at least one of hexadecyltrimethylammonium bromide, polysorbate and alkylphenol polyoxyethylene ether.
7. The method for preparing a lithium iron phosphate positive electrode material for a lithium ion battery according to claim 1, characterized in that: The calcination temperature is 700-850° C. and the calcination time is 10-12 hours.
8. The method for preparing a lithium iron phosphate positive electrode material for a lithium ion battery according to claim 1, characterized in that: The temperature of the microwave treatment is 600-700° C. and the insulation time is 20-40 minutes.
9. A lithium iron phosphate positive electrode material for a lithium ion battery, characterized in that: The lithium iron phosphate positive electrode material for lithium ion batteries is prepared by the preparation method of any one of claims 1 to 8.
10. The lithium iron phosphate positive electrode material for lithium ion battery according to claim 9, characterized in that: The lithium iron phosphate positive electrode material for lithium-ion batteries at least comprises a sodium-manganese co-doped lithium iron phosphate matrix, and a composite coating layer of MXene / reduced graphene oxide and carbon coated on the surface of the lithium iron phosphate matrix.
Citation Information
Patent Citations
Method for producing iron lithium manganese phosphate composite positive electrode material used in lithium ion battery through carbon reduction
CN102364726A
Positive electrode material of lithium ion battery and preparation method thereof
CN104953118A
Olivine type composite positive electrode material, preparation method and application thereof, and lithium ion battery
CN115101734A
Positive electrode material, preparation method thereof and lithium ion battery
CN115548307A
Double-carbon-layer heterogeneous composite positive electrode material, preparation thereof and sodium ion battery
CN116741975A